High-Resolution Resistivity Analysis of Andesite Rock Distribution in Kulon Progo’s Mineral-Rich Terrain - Rizqi Prastowo; Oky Sugarbo; Nanda Juli Setiawan; Setyo Pambudi; Yogesh Murkute; Vishal R. Panse (International Journal of Hydrological and Environmental for Sustainability, 2025)
This study employs integrated geophysical methods to analyze the spatial distribution and subsurface geometry of andesitic rock formations in the Mujil Hill area, Kulon Progo, Yogyakarta. Electrical resistivity imaging (ERI), using a dipole-dipole configuration, was conducted to identify high-resistivity zones (>1000 Ωm), which are interpreted as fresh andesitic intrusions. These zones are consistently found at an average depth of 10 meters, embedded within moderately resistive volcanic breccia. Near-surface layers with low resistivity values (<100 Ωm) are associated with weathered volcanic deposits or unconsolidated soil. To enhance subsurface structural interpretation, resistivity data were complemented with gravity modeling, providing a more comprehensive geological assessment. The results confirm the lateral continuity and shallow emplacement of andesite bodies, highlighting their potential as a local source of construction material. This integrated geophysical approach supports sustainable mineral resource development and aligns with the objectives of the regional economic empowerment program, contributing to the responsible utilization of local geological resources.